Coordinated control of multi-actuated electric vehicle - Barys Shyrokau (2014)
Modern vehicles have the tendency to embed multiple actuators operating jointly to control the motion stability, handling, energy consumption and other operation characteristics. In the thesis, a new solution is provided to the integrated vehicle dynamics control with the prioritization of several vehicle subsystems. The multi-actuated vehicle configuration includes (i) friction brake system, (ii) individual-wheel electric powertrain, (iii) wheel steer actuators, (iv) camber angle actuators, (v) dynamic tire pressure system and (vi) actuators generating additional normal forces. The novel algorithms of subsystem prioritization were proposed based on restriction weights in control allocation. These algorithms achieve lower energy consumption and energy losses without significant impairment to motion stability and vehicle handling as compared to conventional control allocation. The proposed control system has been successfully validated using a hardware-in-the-loop test rig with hardware components of friction brake system and dynamic tire pressure system.